Islam and Secularism: Where the Unlike Charges Repel - Samaila, Ali; Kumo, Aishatu Abubakar; Hassan, Saleh; Yahaya, Nasir; Bello, Rabiu Abdulmudallib (Pascasarjana IAIN Metro, 2024)
Since the advent of secularism in the middle-ages there exist a strong debate among Muslim scholars and thinkers on its compatibility with Islam. The proponents of secularism popularly known as secular Muslims upheld that Islam and secularism are two sides of the same coin because of their shared aspects while its opponents (the Islamists) uphold otherwise. This paper depends on convergence theory to argue that there are some similarities as well as differences between the two concepts. The study suitably adopted descriptive and comparative approaches of qualitative research to generate and analyses data. The study found that there are two types of secularism namely: the radical and moderate secularism. The radical secularism which is usually translated as “extremist” is characterized by hostile approaches to religion while the moderate secularism known as soft secularism acknowledges religious freedom, tolerance and pluralism which are all inherent in the Islamic world views. The major differences between the Islamic world views and that of the moderate secular views lie in the fact that Islam calls for humanity to embrace its faith (Da’awa) in spite its strong position on religious freedom and the Islamic concept of moderation (Wasatiyyah) which advocates upholding balance stance between two opposing extremes. On a final note the research recommends that Muslims should strongly uphold the Islamic teachings in their individual and societal lives alike.